TRANSPLANTATION FOR MANTLE CELL LYMPHOMA: IS IT THE RIGHT TREATMENT OPTION FOR PATIENTS? CASE REPORT - Krstevska Balkanov, Svetlana; Stojanovska, Simona; Nikolova, Dragica; Veljanovska, Aleksandra Pivkova; Trajkova, Sanja; Panovska Stavridis, Irina; Kocoski, Bozidar; Ridova, Nevenka (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Mantle cell lymphoma is clinically and biologically heterogeneous disease, ranging from the indolent non-nodal leukemic variant to the highly malignant blastoid variant. Despite many recent therapeutic advances, mantle cell lymphoma (MCL) remains a largely incurable disease. The median age at diagnosis of MCL is 60–65 years. MCL usually presents with advanced extra nodal, bone marrow, peripheral blood, spleen, and gastrointestinal involvement. First-line treatment consists of chemoimmunotherapy, which may result in prolonged remission, but relapse should be expected. Sustained long-term remissions are achievable following autologous stem cell transplantation. In this case report, we present a case of MCL in 60-year-old men diagnosed initially presented with an abdominal tumor. The patient underwent autologous stem cell transplantation after achieving first remission. Keywords:  MCL, autologous stem cell transplantation, Bruton tyrosine kinase (BTK) inhibitors.